2015
DOI: 10.1093/hmg/ddv182
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in the PP2A regulatory subunit B family genesPPP2R5B,PPP2R5CandPPP2R5Dcause human overgrowth

Abstract: Overgrowth syndromes comprise a group of heterogeneous disorders characterised by excessive growth parameters, often in association with intellectual disability. To identify new causes of human overgrowth, we have been undertaking trio-based exome sequencing studies in overgrowth patients and their unaffected parents. Prioritisation of functionally relevant genes with multiple unique de novo mutations revealed four mutations in protein phosphatase 2A (PP2A) regulatory subunit B family genes protein phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 14 publications
0
65
0
Order By: Relevance
“…Both these phosphatases have been implicated in a wide variety of psychiatric illness such as Alzheimer’s disease [118,119], intellectual disability [120122] and drug addiction [123,124]. Recently PP2A was linked to psychiatric illness and depression-like phenotypes through both animal behavior and genetic screens [125,126].…”
Section: Physiological Consequences Of Camp Regulation Of Pp1 and Pp2mentioning
confidence: 99%
“…Both these phosphatases have been implicated in a wide variety of psychiatric illness such as Alzheimer’s disease [118,119], intellectual disability [120122] and drug addiction [123,124]. Recently PP2A was linked to psychiatric illness and depression-like phenotypes through both animal behavior and genetic screens [125,126].…”
Section: Physiological Consequences Of Camp Regulation Of Pp1 and Pp2mentioning
confidence: 99%
“…While cancer remains the most researched disease context for PP2A disruption, PP2A inhibition also contributes to pathogenesis in cardiovascular disease [1-3], diabetes [4-7], neurodegenerative disease (e.g. Alzheimer’s and Parkinson’s disease) [8-12] and developmental conditions involving intellectual disability [13, 14]. Consequently, therapeutic targeting of PP2A has become an exciting area of research with promising potential for clinical impact across fields.…”
Section: Introductionmentioning
confidence: 99%
“…Both proteins are present at the Drosophila NMJ (Cheng et al, 2011; Viquez et al, 2009, 2006) Single-cell Patch-Seq experiments confirmed the expression of these genes in Drosophila motoneurons at third-instar (Figure S1). Intriguingly, the PPP2R5D gene has recently been associated with intellectual disability and autism in human (Loveday et al, 2015; Shang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%